(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2019)
Having regard to the topic of negligence in medical activities, the main challenge that Italian Criminal Law has to face with, consists in finding a juridical approach useful to recombine the rigid deontology of the general and abstract law which defines a crime, on the one hand, and the high complexity and uniqueness of each clinical case, on the other. A good solution can be found by careful building the model agent as standard of any evaluation concerning negligence. Such a model has to be neither too similar to the concrete physician, otherwise the negligence as mens rea requirement could never be affirmed, nor too similar to an abstract omniscient metaphysical doctor, otherwise it could become source of precautionary rules that are unrecognizable and therefore dysfunctional for the ordinary clinical activity. The best compromise can be found by paying attention to the particular features of this activity, that is by considering the reasons why the sanitary professions is not actually comparable to other typologies of human behaviors that can be considered from the point of view of the negligence. This essay makes a constructively critical analysis of several different approaches of scholars, tribunals and legislator to this kind of issues, with particular regard to the more recent Italian laws on medical responsibility, that have developed the parameter of guidelines.